Approaches to identifying insurance groups - BILA, Daryna (Scientific journal «World of Finance», 2019)
Introduction. The insurance group existence in the market and risks that are associated with insurance groups’ activities are led to the urgency of scientific research and determining the approaches to identify the insurance groups in Ukraine.Purpose. To study the international experience and national practice of the insurance groups identification and the insurance groups’ impact estimation on the insurance market.Results. The article analyzes the foreign practice of the insurance groups identification, the background of the IAIS emphasize the concept of “international insurance group” and the list of the insurance group identification criteria. The author examined the financial group creation ap-proaches: permissive, mixed, separate; and the insurance group identity indicators in Ukraine that are adopted by the NationalCommission for the Financial Service Markets Regulation of Ukraine. Author revealed the presence of insurance groups in the domestic insurance market that are controlled by international financial conglomerates; analyzed the insurance groups’ activity in Ukrainian market and studied their composition. The article contains the list of the insurance group performance indicators that are provided by the regulator; discloses the approach drawbacks that is developed by the National Commission for the Financial Service Markets Regulation for classifying companies as non-bank financial groups. Conclusion. The author formed the proposals that are aimed at improving transparency in the insurance market of Ukraine, such as: publication of information about the implementation of non-bank financial group of the regulatory requirements for regulatory capital adequacy. The article illuminates the financial performance indicators information of non-bank financial groups.